Analytical validation of the iSED automated analyzer for erythrocyte sedimentation rate. (14th November 2019) - Lapić, Ivana; Miloš, Marija; Tosato, Francesca; Piva, Elisa; Zadro, Renata; Rogić, Dunja; Plebani, Mario
Abstract: Introduction: iSED is an alternate automated analyzer for erythrocyte sedimentation rate (ESR) based on photometric rheology technology that estimates ESR by measuring rouleaux formation. The aim was to evaluate the analytical performance of the iSED analyzer and compare the results with the Westergren method and another alternate ESR analyzer, TEST1. Methods: Validation was performed at two study sites according to the recommendations by the International Council for Standardization in Haematology and included determination of intrarun precision and inter‐run precision, bias, carryover, and method comparison, which was further assessed for samples with normal and low hematocrit, as well as per low, middle, and upper third of the analytical range. Results: Intrarun coefficients of variation (CVs) with commercial controls were 4.0% and 1.8%, while inter‐run CVs 7.5% and 0.7%, for the normal and pathological range, respectively. Intrarun CVs obtained with patient samples were 19.9%, 9.9%, 10.3%, and 9.4%, the highest being for the lowest ESR value. Correlation coefficients for the comparison between iSED and Westergren were 0.862 (Site‐1) and 0.916 (Site‐2). While proportional difference with a positive bias was revealed at Site‐1, comparison at Site‐2 showed both constant and proportional difference and a negligible negative bias. Higher correlation was obtained for samples with low than normal hematocrit. Comparison between iSED and TEST1 yielded a correlation coefficient of 0.986, constant and proportional difference, and positive bias. Carryover was 3.2%. Conclusion: This study proved the analytical validity of the iSED analyzer, despite minor discrepancies to the Westergren method that can be attributed to methodological differences.